Pengaruh Pemberian Pursed Lip-Breathing, Diaphragmatic Breathing, dan Upper Limb Stretching Terhadap Skala Dispnea pada Pasien PPOK: The Effect of Pursed Lip-Breathing, Diaphragmatic Breathing, and Upper Limb Stretching on Dyspnea Scale in COPD Patients - Imron Rosyadi; Defriman Djafri; Dally Rahman (NERS Jurnal Keperawatan, 2019)
Respiratory muscle weakness in patients with Chronic Obstructive Pulmonary Disease (COPD) is a problem that can affect the patient's ability to conduct daily activities. The aim of this study to see the difference between the intervention group given the pursed-lip breathing exercises, diaphragmatic breathing, and upper limb stretching with the control group which not given therapy. 38 COPD patients were grouped into intervention groups (n = 18) and control group (n = 18) randomly. The intervention group was given pursed-lip breathing, diaphragmatic breathing, and upper limb stretching for 4 weeks as much as two times for each week, while the control group was not given exercise. The dyspnea scale was measured using the MRC Dyspnea Scale questionnaire and was categorized as mild (scale 1), medium (scale 2-3) and severe (scale 4-5). The result showed there was a difference in dyspnea (p value 0.008) for intervention group and there is no difference in the dyspnea for control group that was not given exercise (p value 0.655). In conclusion, pursed lip breathing, diaphragmatic breathing, and upper limb stretching can give more significant benefits when done sustainably, especially for COPD patients.